BAFF/APRIL System Is Functional in B-Cell Acute Lymphoblastic Leukemia in a Disease Subtype Manner - Sevdali, Eirini; Katsantoni, Eleni; Smulski, Cristian R.; Moschovi, Maria; Palassopoulou, Maria; Kolokotsa, Eleni-Nefeli; Argentou, Nikoletta; Giannakoulas, Nikolaos; Adamaki, Maria; Vassilopoulos, Georgios; Polychronopoulou, Sophia; Germenis, Anastasios E.; et al. (Frontiers in Oncology, 2019)
BAFF, APRIL and their receptors regulate the survival, maturation and homeostasis of mature B-cells. Despite the lack of a functional role of BAFF/APRIL system during normal early B-cell development, previous studies indicated a contribution of these molecules in the pathogenesis of B-lineage acute lymphoblastic leukemia (B-ALL). Here, we evaluated the expression of this system in B-ALL and its involvement in spontaneous and drug-induced apoptosis of B-lymphoblasts, taking into consideration the distinct disease subtypes. We found that BAFFR is the most predominant aberrantly expressed receptor in B-ALL and that its expression, along with BCMA and APRIL, positively correlates with the maturation stage of B-lymphoblasts. Moreover, the binding of the E2A-PBX1 chimeric protein to the BAFFR promoter suggests that the transcriptional activator promotes the increase in BAFFR expression observed in about 50% of pre-B-ALL patients carrying the t(1, 19) translocation. BAFF binding to BAFFR led to the processing of NF-κB2 p100 in pre-B ALL cells suggesting that BAFFR can activate the NF-κB2 pathway in pre-B ALL cells. Surprisingly, we found that BAFF treatment promotes the cell death of primary BCR-ABL+ BAFFR+ pre-B-lymphoblasts in adult B-ALL. It also enhances glucocorticoid-induced apoptosis in the E2A-PBX1+ pre-B-ALL cell line 697. These data suggest that BAFF/BAFFR signaling in B-ALL cells differs from normal B cells and that it may affect the pathogenesis of the disease.